Mathematical Study of Two-Dimensional Temperature Variation in Tumor Embedded Breast Tissue - Shrestha, Sharmila; KC, Gokul; Gurung, Dil Bahadur (The Nepali Mathematical Sciences Report, 2021)
The human body is made by 100 trillion cells. The uncontrolled and abnormal growth of cells causes tumors. Due to the presence of tumor, the skin surface temperature of body provides abnormal behavior than normal. Most of the breast tumor develops in lobules and milk ducts of glandular layer. In this study, tumor is assumed in glandular layer. The study of this work is focused to find the temperature distribution in tumor embedded female breast tissue with different tumor location and different tumor size. For this, the finite element method is used to solve two-dimensional Pennes bio heat equation. The results show that the skin surface temperature of breast is higher with nearest tumor from areola. The temperature variation in breast tissue with tumors located at symmetrical position about the central line of the breast are identical.